(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Kirab Jenang Tebokan tradition in Kaliputu Village, Kudus Regency, is a cultural ritual that has a deep meaning in the social life of the local community. This tradition has been going on since 2006 by passing through the road corridors around Kaliputu Village. Still, in 2018, the procession’s route changed by passing through the main road of Kaliputu Village to Kaliputu Village Hall. In this case, the tradition functions as a cultural celebration involving the community and as a representation of the dynamics of cultural space built during the procession. Kirab Jenang Tebokan creates temporary spaces full of social value where people gather, interact, and share in a family atmosphere. The implementation of route changes in the procession causes changes in the meaning of cultural space, which becomes the spatial embodiment of the Kirab Jenang Tebokkan tradition. This research examines the dynamics of cultural space formed during the Kirab Jenang Tebokan procession, as well as how the community uses and interprets the space. This research method uses a qualitative approach through field observations and interviews with traditional leaders and local people involved in the activity. The results showed that changes in the route of the curb affected the pattern of social interaction, accessibility, and people’s perceptions in interpreting the cultural space formed during the procession. In addition, these changes can expand community involvement and strengthen local cultural identity. The implications of this research can provide insights for stakeholders, architectural practitioners, and academics in planning local culture-based public spaces.